Saksi Pejabat Notaris dalam Persidangan Perdata: Studi Kasus Pengadilan Negeri Semarapura Bali Nomor 53/Pdt.G/2020/PN.SRP Tanggal 05 November 2020 - Silaen, Petrus Edison; Kamelo, Tan Edison; Agustining, Agustining; Sidabariba, Burhan (Journal of Law & Policy Review, 2023)
Notaries/PPAT can act as plaintiffs' witnesses if they are aware of incidents that become the core of disputes beyond their notarial duties. This study discusses the presence of Notaries/PPAT as plaintiffs' witnesses based on Civil Law and Law Number 2 of 2014 concerning the position of Notaries. A case study was conducted on the decision of the Semapura Bali District Court Number 53/PDT.G/2020/PN.SRP on November 5, 2020. This research is normative legal and socio-legal research with a descriptive-analytic approach. Data were collected from secondary and primary sources and analyzed qualitatively. The results show that the presence of Notaries/PPAT as plaintiffs' witnesses considers Civil Law and the Law concerning the position of Notaries/PPAT. The presence of Notaries/PPAT as plaintiffs' witnesses can be rejected based on the right of refusal regulated by the law. The Notary Honorary Board (MKN) acts as legal protection, assesses the authority of Notaries/PPAT, and maintains confidentiality by legal provisions. The role of Notaries/PPAT as a witness in court is to provide legal explanations.